Literacy Quebec Newsletter - Literacy Quebec (LQ) (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by theSecrétariat aux relations avec les Québécois d’expression anglaise from December 2021to the present.
Keywords: Official Language Minority Community (OLMC)

Championing Early Literacy Through Libraries and Community Partnerships - Dixit, Aisha (QUESCREN Education and Vitality Forum 2023, 2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Consultation prébudgétaire de Alphabétisation Québec 2023-2024 déposé au ministre des Finances du Québec et au ministre responsable des Relations avec les Québécois d’expression anglaise - Literacy Quebec (LQ) (2023)
Alphabétisation Québec/Literacy Québec est un regroupement national qui compte 15 organismes d’alphabétisation populaires. Fondé en 1980, il est accrédité au Programme d’action communautaire sur le terrain de l’éducation (PACTE) et reçoit un soutien financier pour appuyer sa mission globale de la part du ministère de l’éducation ainsi que du Secrétariat aux relations avec les Québécois d’expression anglaise. Le regroupement mène des actions pour conscientiser le public aux réalités de l'analphabétisme et pour promouvoir des opportunités d’apprentissage tout au long de la vie. Alphabétisation Québec offre du soutien, de l’accompagnement et de la formation continue à ses groupes membres. Ceux-ci sont des milieux de vie et des lieux de formation pour les adultes et les familles de toutes origines qui désirent acquérir, rehausser ou maintenir leurs compétences de base sur le plan de la lecture, l’écriture, la numératie ou la littératie numérique. Ils ont développé une approche unique d’éducation non formelle et informelle qui vise l’autonomisation et l’inclusion des personnes et qui est adaptée au rythme d’apprentissage des participants.

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter : Special Edition - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Society Pages - Morrin Centre (2022)

Society Pages - Morrin Centre (2022)

COVID-19 Survey Report II - Literacy Quebec (LQ) (2021)
While the pandemic has forced a lot of swift changes, the majority of Literacy Quebec's member organizations have been able to adapt. In fact, 8 out of 9 respondents claimed to have successfully transitioned at least some of their programs and services online. However, while most organizations were able to move to some type of online- learning model, a select few reported having no available tutors/volunteers. Some of the reasons ranged from a lack of interest (i.e. volunteers originally signed up to interact with others in person), or a lack of confidence in using technology.

Activity Report - Literacy Quebec (LQ) (2021)

Family Literacy Toolkit - Literacy Quebec (LQ) (2021)

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

Annual Activity Report : June 1, 2018 - May 31, 2019 - Literacy Quebec (LQ) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

Annual Activity Report : June 1, 2017 - May 31, 2018 - Literacy Quebec (LQ) (2018)
Literacy Quebec provided ongoing support to its members by offering training and assistance via web, email and telephone. The LQ staff fielded and responded to 950+ enquiries and concerns from its membership. They also sent out 30 email updates throughout the year. Members were brought together once in person and once via web-conference for professional developments and networking opportunities.
Keywords: Official Language Minority Community (OLMC)

Annual Activity Report : June 1, 2016 - May 31, 2017 - Literacy Quebec (LQ) (2017)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once via conference call for professional development and networking opportunities. Through a PACTE funded project, Literacy Quebec was able to develop tools to strengthen its network. The project allowed us to examine new ways of promoting literacy and explaining the issues surrounding low literacy to the general public. The project also enabled the organization to engage more volunteers and pilot a database to track volunteers, supporters, members, etc.

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

Annual Activity Report : June 1, 2015 - May 31, 2016 - Literacy Quebec (LQ) (2016)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once online via web-conference for professional development sessions and networking opportunities.

Letter to the Minister of Education, Higher Education and Research - Legault, Margo; Brassard, François (2016)

Lettre au ministre de l’Éducation, de l’Enseignement supérieur et de la Recherche - Legault, Margo; Brassard, François (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

Youth at Risk and the Writers in the Community Program : An Exploratory Evaluation - Hanley, Jill (The Centre for Literacy of Quebec (CFL), 2014)
Given its central importance to modern life, literacy has long been seen as both a challenge and an opportunity for members of marginalized populations (Movement for Canadian Literacy, 2001; Neuman, 2008), including youth at risk (Walker, Greenwood, Hart, & Carta, 1994; Willms, 1997). Such youth face many barriers to success at school and when they leave school with weak literacy skills, they face further challenges to employment and interaction with public institutions. On the other hand, helping youth at risk to develop stronger literacy skills – and, in the best case scenario, a love of reading and writing – may not only address practical challenges to future employment and public engagement (StatsCan, 2006) but can also make a significant contribution to positive self-esteem and positive relationships with their peers, teachers and parents (Chandler, 1999).

International Adult Skills Surveys: Andragogical Issues in Linguistic Minority Communities - Lurette, Donald (The Centre for Literacy of Quebec (CFL), 2014)
I have been working in the literacy field with francophone adults in a minority setting and in a variety of capacities for twenty years, and consider myself a reflective and critical practitioner. I strive to understand the world of adult education and skills development based on my practical experiences and observations from the field. This text is written from that perspective, based on principles of andragogy. Using inductive and deductive processes, I propose ideas and reflections on the concept of the evaluation of basic skills of adults living in linguistic minority communities in Canada. On the theoretical side, I use several key studies, including an analytical background paper written for The Centre for Literacy’s 2013 Summer Institute by Jean-Pierre Jeantheau, Chargé de mission national of the French Agence nationale de lutte contre l'illettrisme, on the subject of linguistic minority groups and international literacy assessments.

Annual Activity Report : June 1, 2013 - May 31, 2014 - Literacy Quebec (LQ) (2014)

PACTE Project 2013-2014 : The Power of an Online Presence, a Skill to be Harnessed. - Literacy Quebec (LQ) (2014)
The following project has been completed by Literacy Quebec by a grant from Opération Projets PACTE As a provincial organization, Literacy Quebec’s mandate is to support community-based literacy organizations that provide service to English-speaking adults in Quebec, through training, networking and professional development.

Western Quebec Literacy Council: Annual Report: 2013-2014 - Western Quebec Literacy Council (2014)

IALS and Essential Skills in Canadian Literacy Policy and Practice : A Descriptive Overview - Hayes, Brigid (2013)
The field of literacy encompasses many disciplines and areas of engagement from early childhood through schooling to community and work contexts over the lifespan. This review is concerned with a sub-set of the field – adult literacy – with a specific focus on the influence of the International Adult Literacy Survey (IALS) on policy and practice across Canada since its release in 1994. With the upcoming release of the Programme for the International Assessment of Adult Competencies (PIAAC) results in Fall 2013, this overview describes some of the ways IALS has been used by Canadian governments and literacy organizations.

Annual Activity Report : June 1, 2012 to May 31, 2013 - Literacy Quebec (LQ) (Literacy Quebec, 2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

The Literacy and Essential Skills Needs of Quebec's Anglophone Adults - Centre for Literacy (CFL) (2012)
Understanding the Literacy and Essential Skills Needs of Quebec’s Anglophone Adults,1 Phase 1, was a project designed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve Englishspeaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities (discussed in detail in Sections Three and Four) which showed large disparities in literacy performance among Quebec Anglophones (Corbeil 2006: 20). The findings suggested differences in needs from one community to another that may require targeted services.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

Understanding Literacy and Family Literacy Needs of Anglophone Adults in Quebec : Research Summaries - The Centre for Literacy of Quebec (CFL) (2011)
The Understanding literacy and family literacy needs of Anglophone adults in Quebec project aimed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve English-speaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities which showed large disparities in literacy performance among Quebec Anglophones. The findings suggested differences in need from one community to another that may require targeted services. This project set out to fill this knowledge gap and to insert LES into the ongoing discussion about Anglophones in Quebec. All Quebec English-language umbrella groups stand to benefit from the findings in terms of proposing better policy, planning new services and using resources more efficiently. There may be opportunities for new partnerships to develop solutions to some challenges not previously seen as linked to literacy. The project will also provide a useful road map for identifying promising new research avenues that would assist LES organizations in getting a more detailed picture of the communities they are aiming to serve.

A Health Literacy Tool Kit for Healthcare Providers : Improving Communication with Clients - Strickland, Kate (Literacy Volunteers of Quebec, 2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2010)

Home Intervention Program for Parents of Pre-School Youngsters (HIPPY): An Efficacy Study - Butler-Kisber, Lynn; Kingsley, Joanne; Sklar, Sylvia (The Centre for Literacy of Quebec (CFL), 2009)
his study was originally commissioned by The Centre for Literacy of Quebec in fulfillment of the terms of HIPPY-Montreal's generous four-year start-up grant from the Fondation Lucie et André Chagnon. The Centre and its partners, the Salvation Army and Elizabeth House, felt that given the unique design and complexity of the HIPPY program, a qualitative study would generate more usable findings than would a solely quantitative one. The Fondation Lucie et André Chagnon had requested that any evaluation of the HIPPY-Montréal program include a quantitative component; so, in addition to their intensive observations of and interviews with HIPPY staff and families implementing the program, the researchers also administered Peabody tests to participating children. This final report on the efficacy of the program includes the results of the testing along with the findings from two years of study.

Report on the Lire/Imagine/Read Project at the Montreal Children's Hospital of the McGill University Health Centre - The Centre for Literacy of Quebec (CFL) (2009)
This project arose from the wealth of information available about the successful U.S. pediatric health care program ”Reach Out & Read”, and the Canadian Pediatric Society initiative ”Read Speak, Sing to your Baby”. There is overwhelming evidence that the promotion of reading by health care professionals. (See rationale and references.)

Recognition awards for adult literacy : Submissions - Quebec Association for Adult Learning (QAAL) (2009)

Pas de talents à perdre : priorité à l’alphabétisation - Charest, Jean; David, Françoise; Dumont, Mario; Khadir, Amir; Marois, Pauline; Rainville, Guy; La Coalition pour l’alphabétisation (2008)

Conference Announcement and Call for Presentations - Quebec Association for Adult Learning (QAAL) (2008)

Recognition awards for adult literacy : Submissions - Quebec Association for Adult Learning (QAAL) (2008)

Adult ESL and Literacy : Issues and Options - Spruck Wigley, Heide (The Centre for Literacy of Quebec (CFL), 2008)
In this paper, I would like to put forward a number of issues for us to think about and discuss. At the same time, I argue for a better articulated system that more closely matches the needs and goals of various subgroups of English language learners.

Health Matters - Coasters Association (2007)

Bridging the Gap Meeting - Literacy Quebec (LQ) (2007)

Literacy Access Project : Lifelong Learning Collections - The Centre for Literacy of Quebec (CFL) (2007)
The Literacy Access Project represents the second phase of a larger initiative undertaken by The Centre for Literacy to formally assess and adjust its local mandate. The ultimate goal of this strategic effort was to formulate a long-term sustainability plan in the context of important changes that have been taking place in the English community in Quebec in recent years. These changes include a shrinking population base, cuts in provincial and federal funding, new responsibilities for school boards, and the recent creation of community learning centres in various regions of the province. On the basis of a 2006 Community Consultation and building on the 2007 Summer Institute on Libraries and Literacy, The Centre determined that it needed to develop more solid and lasting links between libraries and literacy groups that support English populations.

QAAL Newsletter - Quebec Association for Adult Learning (QAAL) (2007)

QAAL Newsletter - Quebec Association for Adult Learning (QAAL) (2007)

Recognition awards for adult literacy : Submissions - Quebec Association for Adult Learning (QAAL) (2007)

E-Newsletter - Quebec Association for Adult Learning (QAAL) (2006)

E-Newsletter - Quebec Association for Adult Learning (QAAL) (2006)

E-Newsletter - Quebec Association for Adult Learning (QAAL) (2006)

Literacy Resource Directory : Prevention Activities in Quebec - Seys, Wendy (Literacy Volunteers of Quebec, 2004)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2003)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2003)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2003)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2002)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2002)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2002)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2002)

Native Literacy Pre-school Education Project - The Centre for Literacy of Quebec (CFL) (The Centre for Literacy of Quebec (CFL), 1999)

Newsletter - The Centre for Literacy of Quebec (CFL) (1999)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Apprentissage des langues dans les écoles anglaises du Québec : Maîtrise impérative des deux langues - Advisory Board on English Education (1995)
La réorganisation des commissions scolaires, qui devra se faire tôt ou tard, entraînera nécessairement d'importantes adaptations de l’enseignement dans le secteur anglophone. La création d’un véritable réseau scolaire anglophone par la fusion des structures catholique et protestante actuelles va permettre de consolider et de rationaliser le système scolaire anglophone de façon efficace, c’est-à-dire de lui donner une mission éducative convenant à tous les éléments de la communauté anglophone et à toutes les écoles qui la servent.

Language Learning in the English Schools of Quebec : A Biliteracy Imperative - Advisory Board on English Education (1995)
The school board reorganization, which sooner or later is bound to come about, will force major adjustments on the delivery of English education. The forming of a true English school network through the fusion of the existing Catholic and Protestant structures will provide both an opportunity to strengthen and rationalize the English school system and a challenge to get it right. By getting it right is meant finding an educational mission to which all the constituencies of the English-speaking community and the schools which serve it can respond.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1986)

Literacy Across the Curriculumedia Focus - Arsenault, Mona

Competency-Based Progress Assessment Skills for Life-long Learning - Literacy Quebec (LQ)

Family Literacy Toolkit : Resources, Planning Guide, Best Practices - Literacy Quebec (LQ)
Literacy Quebec is a network that connects and represents community-based literacy organizations to empower people, impact lives and build a stronger society. We envision a Quebec where everyone has the literacy skills they need to live a fully engaged life.

L’alphabétisation, c'est beaucoup plus que l'abc : C’est un enrichissement pour nos communautés - Literacy Volunteers of Quebec

Born to Read / Le goût de lire - Quebec Federation of Home and School Associations (QFHSA)

Great Read Aloud Books - Quebec Federation of Home and School Associations (QFHSA)

Noise and Learning - Quebec Federation of Home and School Associations (QFHSA)

Pre-School Language Development - Quebec Federation of Home and School Associations (QFHSA)

Read to Your Baby : Doctor's Orders - Quebec Federation of Home and School Associations (QFHSA)

Success Story : Born to Read - Quebec Federation of Home and School Associations (QFHSA)

The Science is In : Literacy Begins at Birth - Quebec Federation of Home and School Associations (QFHSA)

Development of ABE/Literacy in Canada : A Chronology - Shohet, Linda

Literacy Across the Curriculumedia Focus - Shohet, Linda

Reaching the Rainbow: Aboriginal Literacy in Canada - Smith, Donna-Lee

HIPPY Montréal : Évaluation des Résultats 2008-2009 - The Centre for Literacy of Quebec (CFL)
HIPPY est un programme de formation à domicile qui montre aux parents comment devenir les premiers enseignants de leurs enfants et préparer leurs tout-petits de 3 à 5 ans pour l’école. Ce rapport fait le bilan des principaux résultats produits par le programme HIPPY à Montréal au cours de l’année 2008-2009. Au cours des quatre dernières années, le programme HIPPY Montréal a réussi à engager plus de 250 familles de diverses communautés immigrantes vulnérables dans son programme d’alphabétisation familiale. Le modèle d’intervention mis de l’avant dans le programme HIPPY utilise des approches éducatives et de développement personnel pour aider à briser l’isolement social, linguistique et économique que vivent plusieurs familles immigrantes qui ont participé au programme.

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL)